2018
DOI: 10.1038/s41598-018-32806-3
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Performance of Zinc-Air Flow Batteries Under the Effects of Sodium Dodecyl Sulfate and Pluronic F-127

Abstract: Zinc-air batteries are a promising technology for large-scale electricity storage. However, their practical deployment has been hindered by some issues related to corrosion and passivation of the zinc anode in an alkaline electrolyte. In this work, anionic surfactant sodium dodecyl sulfate (SDS) and nonionic surfactant Pluronic F-127 (P127) are examined their applicability to enhance the battery performances. Pristine zinc granules in 7 M KOH, pristine zinc granules in 0–8 mM SDS/7 M KOH, pristine zinc granule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 40 publications
(40 reference statements)
0
80
0
Order By: Relevance
“…The formation of ZnO, on the forward scan, was followed by its precipitation on the electrode surface, thus forming a passive layer which reduced the active area of the electrode. However, the Zn ions which did not oxidize in the forward scan tended to oxidize in the reverse scan, due to the breakdown of the passive layer at the very oxidation potential range [32]. The Zn/IF electrode exhibited a smaller oxidation peak in reverse scan that slightly shifted to negative potentials, suggesting that the passivation film was more stable and less soluble in the presence of the fibrous iron electrode.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of ZnO, on the forward scan, was followed by its precipitation on the electrode surface, thus forming a passive layer which reduced the active area of the electrode. However, the Zn ions which did not oxidize in the forward scan tended to oxidize in the reverse scan, due to the breakdown of the passive layer at the very oxidation potential range [32]. The Zn/IF electrode exhibited a smaller oxidation peak in reverse scan that slightly shifted to negative potentials, suggesting that the passivation film was more stable and less soluble in the presence of the fibrous iron electrode.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…According to CV analysis, the Zn/IF electrode revealed a comparable mechanism of Zn dissolution/deposition with the Zn/NF electrode. Although the surface of Zn/IF is susceptible to corrosion via hydrogen evolution, the impact can be diminished when using additives to the electrolyte solution [32]. Furthermore, the IF electrode displayed a noticeably low charge transfer resistance and, hence, proved to be a preferable substitute to the conventional NF in the synthesis of the porous anode.…”
Section: B)mentioning
confidence: 99%
“…As regards air cathode polarization, the zinc-air battery was fabricated using the 0.3 M AgNP/rGO catalyst with different ratios of AgNP/rGO to carbon black: namely, 9:0, 7:2, 5:4 and 3:6. The air-cathode made of MnO 2 to carbon black of 2:7, which is generally used as ORR electrocatalyst [42,43], was also included, as a reference, to compare the performance of the synthesized electrocatalysts. Figure 5a shows the overpotential of the air cathodes.…”
Section: Performances Of Zab Using the Synthesized Agnp/rgo Electrocamentioning
confidence: 99%
“…This problem was partially solved by using a complete gel electrolyte like anionic surfactant sodium dodecyl sulfate (SDS) or nonionic surfactant Pluronic F‐127 that might effectively suppress the anode corrosion and passivation. Galvanostatic discharge results indicated that the improvement of discharge capacity can be achieved by using surfactants to the KOH electrolyte . Implementation of a circulating electrolyte flow system will result in the removal of spent Zn anode, and in the meantime, the Zn fuel can also be continually added to the reaction tank via the flowing electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Galvanostatic discharge results indicated that the improvement of discharge capacity can be achieved by using surfactants to the KOH electrolyte. 7 Implementation of a circulating electrolyte flow system will result in the removal of spent Zn anode, and in the meantime, the Zn fuel can also be continually added to the reaction tank via the flowing electrolyte. The reactant elimination can still be resupplied smoothly without using a mechanical exchange.…”
Section: Introductionmentioning
confidence: 99%